Teacher and Students' Perceptions in Using Quipper School in English Teaching and Learning During Pandemic Related to Islam and Science - Retno Ayu Cahyaningtyas; Dyah Kusumastuti (Alhamra Jurnal Studi Islam, 2022)
The COVID-19 pandemic is not over yet. Rasulullah SAW taught that when a pandemic occurs, we must avoid the outbreak, this is also in accordance with government policy, which is to change the learning system to online. This study investigated how teachers and students perceive the use of an online platform, namely Quipper School, in the implementation of English learning. The researcher used a qualitative descriptive method by observing the implementation of learning and interviewing 1 teacher and 5 students. The researcher concluded that the interest of teachers and students in using the Quipper platform was quite low. In addition, there were many challenges that must be faced by teachers, one of which was the low motivation of students in learning during the pandemic. Therefore, a teacher needs to increase the spirit of learning to his students in accordance with Islam and science.